Synthesis and Characterization of Diosgenin Encapsulated Poly-ε-Caprolactone-Pluronic Nanoparticles and Its Effect on Brain Cancer Cells - Bijuli Rabha (Polymers, 2021)
Diosgenin encapsulated PCL-Pluronic nanoparticles (PCL-F68-D-NPs) were developed using the nanoprecipitation method to improve performance in brain cancer (glioblastoma) therapy. The nanoparticles were characterized by dynamic light scattering (DLS)/Zeta potential, Fourier-transform infrared (FTIR) spectra, X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), and Transmission electron microscopy (TEM). The encapsulation efficiency, loading efficiency, and yield were calculated. The in vitro release rate was determined, and the kinetic model of diosgenin release was plotted and ascertained. The cytotoxicity was checked by MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide)assay against U87-MG cells (glioblastoma cell lines). The obtained nanoparticles demonstrated good size distribution, stability, morphology, chemical, and mechanical properties. The nanoparticles also possessed high encapsulation efficiency, loading efficiency, and yield. The release rate of Diosgenin was shown in a sustained manner. The in vitro cytotoxicity of PCL-F68-D-NPs showed higher toxicity against U87-MG cells than free Diosgenin.